Studi Eksperimental Penggunaan Reaktor Microbial Fuel Cell (MFC) Dengan Membran Berongga Sebagai Alat Memanen Energi Terbarukan Dari Variasi Limbah Organik - umi nihayah; M. Ramdlan Kirom (The International Journal of Pegon : Islam Nusantara civilization, 2022)
dengan bantuan mikroorganisme. Pada penelitian ini menggunakan desain dual chamber MFC 10x10x5 cm untuk mengetahui keluaran arus dan tegangan yang dihasilkan menggunakan membran berongga semen ukuran diameter 3 cm dan tebal 0,5 cm dengan campuran Natrium Clorida (NaCl). Kompartemen anoda menggunakan plat seng (Zn) dan katoda menggunakan plat tembaga (Cu) dengan ukuran sama 5x3 cm. Penelitian menggunakan perbandingan 1:1 untuk variasi limbah organik substrat limbah cair tahu dan limbah kulit pisang dengan dicampur lumpur sawah. Dari hasil pengukuran, produksi listrik maksimal selama 14 hari pada substrat limbah cair tahu yaitu dengan inkubasi 6 hari dan pada substrat limbah kulit pisang padat dan cair yaitu dengan inkubasi 3 hari. Hasil pengukuran dapat diperoleh tegangan 252,010 mV, arus 2,52 mA, dan daya 390,648 mW pada substrat limbah cair tahu, tegangan 82,609 mV, arus 0,828 mA, dan daya 68,543 mW pada substrat limbah kulit pisang padat, dan tegangan 66 mV, arus 0,66 mA, dan daya 43,6 mW pada substrat limbah kulit pisang cair. Currently, Indonesia has a big challenge to increase quality energy in order to support sustainable development. So far, the energy used to produce electricity is oriented towards fossil energy which causes negative impacts, while the utilization of non-fossil energy is still low. The solution provided is the use of new and renewable energy that can be used for electricity production needs such as the use of Microbial Fuel Cell (MFC) technology. MFC is a bioelectristry-based device that converts chemical energy into electricity by utilizing organic compounds as well as utilizing enzymatic catalysts with the help of microorganisms. In this study, it used a dual chamber MFC 10x10x5 cm design to determine the output of current and voltage generated using a cement hollow membrane measuring 3 cm in diameter and 0.5 cm thick with a mixture of Sodium Clorida (NaCl). The anode compartment uses zinc plate (Zn) and the cathode uses copper plate (Cu) with the same size of 5x3 cm. The study used a ratio of 1: 1 for the variation of organic waste substrates of tofu liquid waste and banana peel waste mixed with rice field sludge. From the measurement results, electricity production is a maximum of 14 days on the tofu liquid waste substrate, namely with 6 days incubation and on the solid and liquid banana peel waste substrate, namely with 3 days incubation. The measurement results can be obtained a voltage of 252,010 mV, a current of 2.52 mA, and a power of 390.648 mW on the tofu liquid waste substrate, a voltage of 82.609 mV, a current of 0.828 mA, and a power of 68.543 mW on the solid banana peel waste substrate, and a voltage of 66 mV, a current of 0.66 mA, and a power of 43.6 mW on the liquid banana peel waste substrate.